Given:
The ellipse has center (2,2), focus (2,0), and vertex (2,5).
The equation of elllipse is given as,
![((x-h)^2)/(b^2)+((y-k)^2)/(a^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/xyy0a5bxau4ae850x86hlehxmqyl7qa4zn.png)
a is the distance between vertex and center.
![\begin{gathered} a=\sqrt[]{(2-2)^2+(5-2)^2} \\ a=\sqrt[]{3^2}=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wi983d5o948e7n19mzodap05frg8nwnmdu.png)
c is distance between focus and center.
![\begin{gathered} c=\sqrt[]{(2-2)^2+(0-2)^2} \\ c=\sqrt[]{4} \\ c=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6fzrnnv6jsu5u08dms2j2gcrunll6tpk1w.png)
It gives,
![\begin{gathered} c^2=a^2-b^2 \\ 2^2=a^2-b^2 \\ b^2=9-4 \\ b^2=5 \\ b=\pm\sqrt[]{5} \\ b=\sqrt[]{5}\ldots\ldots\text{ Since b is distance and it should be positive} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/n66nqsrj64fm7xbodkgwauix7sm6tk410n.png)
So, the equation of the ellipse is,
![\begin{gathered} ((x-h)^2)/(b^2)+((y-k)^2)/(a^2)^{}=1 \\ \frac{(x-2)^2}{(\sqrt[]{5})^2^{}}+((y-2)^2)/(3^2)=1 \\ \frac{(x-2)^2}{5^{}}+\frac{(y-2)^2}{9^{}}=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/qpr7lfzadkxy6593wwibs7tbp3318x40m7.png)
Answer: option b)